Hydrologic and geomorphic changes resulting from episodic glacial lake outburst floods: Rio Colonia, Patagonia, Chile. Issue 2 (21st January 2017) - Jacquet, J.; McCoy, S. W.; McGrath, D.; Nimick, D. A.; Fahey, M.; O'kuinghttons, J.; Friesen, B. A.; Leidich, J.
Abstract: Glacial lake outburst floods (GLOFs) are a prominent but poorly understood cryospheric hazard in a warming climate. We quantify the hydrologic and geomorphic response to 21 episodic GLOFs that began in April 2008 using multitemporal satellite imagery and field observations. Peak discharge exiting the source lake became progressively muted downstream. At 40–60 km downstream, where the floods entered and traveled down the main stem Rio Baker, peak discharges were generally < 2000 m 3 s −1, although these flows were still >1–2 times the peak annual discharge of this system, Chile's largest river by volume. As such, caution must be applied to empirical relationships relating lake volume to peak discharge, as the latter is dependent on where this observation is made along the flood path. The GLOFs and subsequent periods of free drainage resulted in > 40 m of incision, the net removal of 25 × 10 6 m 3 of sediment from the source lake basin, and a nonsteady channel configuration downstream. These results demonstrate that GLOFs sourced from low‐order tributaries can produce significant floods on major main stem rivers, in addition to significantly altering sediment dynamics. Key Points: Glacial lake outburst floods (GLOFs) from a low‐order tributary increased the magnitude and frequency of floods on Chile's largest river A net of 25 × 10 6 m³ of sediment was removed from the dammed lake basin during GLOFs and subsequent times of free drainage from 2008 to 2015 Along the Rio Colonia braid plain, GLOFs produced a nonsteady state channel configuration